Tendencias estacionales de la precipitación en la cuenca del Ebro 1951-2000 - De Luis, M.; Longares, L.A,.; Stepanek, P.; González-Hidalgo, J.C. (Geographicalia, 2015)
We have analyzed seasonal and annual precipitation trend in the Ebro catchment (NE Spain) during the second half of XXth (1951 2000). Data analyzed come from monthly precipitation data base of Mediterranean Spain (MOPREDAMES). The total amount of rainfall series is 424 and the mean value of spatial density is 1 observatory per 200 km2; data base include information in altitude until 1250 m osI. The results allow us to suggest that in the Ebro catchment during the second half of the XXth century annual precipitation has slight decreased in 3/4 of total stations. At seasonal scale the most generalized decreasing of precipitation is found during summer (44% of total stations). Significant decreasing affects 1/3 of total stations in winter, spring and fall. Spatial differences can be described. In winter precipitation shows a generalized negative trend but mainly not significant. During spring and summer we have detected slight increment in the upper catchment area, while left margin of the Ebro catchment has been under negative and significant trend. A clear difference exits from N to S during autumn, with positive and negative trend respectively.